Philippine medical thesaurus on anatomy digestive system, respiratory system, urogenital system and diseases : pathological conditions, signs and symptoms in Pangasinan - Hombrebueno, Andre Karlo G. (2005)
This study entitled "Philippine medical thesaurus on anatomy: digestive system, respiratory system, urogenital system and diseases: pathological conditions, signs and symptoms" is one of the many contributions to the development of a Multilingual Philippine Medical Thesaurus. The Multilingual Philippine Medical Thesaurus project is a part of the collaborative efforts of the Institute of Library and Information Science, University of the Philippines Diliman, and the College of Medicine, University of the Philippines Manila which started in 2002.